FUNGSI DINAS TENAGA KERJA DAN TRANSMIGRASI PROVINSI NTT DALAM PEMBERDAYAAN MASYARAKAT SEBAGAI TENAGA KERJA LOKAL - Baoh, Gregorius J; Monteiro, Josef M; Lamataro, Cyrilius W T (Petitum Law Journal, 2025)
This research examines the role of the Department of Manpower and Transmigration of East Nusa Tenggara Province in empowering the community as local labor. Using an empirical juridical approach, this study explores how the department formulates and implements labor and transmigration policies, including the evaluation and reporting functions, as well as additional tasks assigned by the governor. Findings show that while several initiatives such as training programs, skill development, and cooperation with vocational institutions have been implemented, significant obstacles hinder their effectiveness. These include limitations in human resources, inadequate infrastructure, and insufficient budget allocations. Moreover, the quality of training often fails to meet the actual needs of local workers, and many potential beneficiaries remain uninvolved or unaware of existing empowerment programs. The study suggests that a more targeted, participatory, and well-supported approach is needed to improve the capacity and competitiveness of local labor in East Nusa Tenggara.